Antipruritic activities of haruan extract on chemically induced itch and dry skin itch mouse model - Muhamad Fauzi, Muhamad 'Irfan (2021)
The objective of this study was to determine the antipruritic activity of Haruan extract against dry skin and chemically induced itch mice models. The study was designed as alternative method, as HE antipruritic potential cream has never been reported for specific dry skin itch. In attempt to established the pharmacological properties of HE, the antipruritic potential of HE was investigated using dry skin itch, histamine-itch and C48/80 itch mouse model. Throughout the study, the animals were divided into 18 groups. Each group divided by different inducer containing 8 mice per group. For the first stage of behavioural study, all rostral back of mice were shaved and acclimatise for 3 days. For dry skin itch model, AEW were topically applied to induce itch twice daily for five consecutive days. Histamine itch model were SC injected with 0.3mg/kg and C48/80 itch model were SC injected with 3.6mg/kg. All models were continuously applied with 3%, 7% and 10% of HE creams and placed in custom chambers on an elevated metal mesh floor and recorded for 30 minutes. The possible effect of Haruan extract cream on TNF-α gene expression level was determined by RNA extraction of skin followed by RT-PCR and analysed by relative quantification using comparative method. The morphological change of the skin was determined by stained with H&A and evaluated of general epidermal thickness using image analyser. The behavioral observed of dry skin itch, histamine, and C48/80 induced mice models were showed reduced in scratch duration shown by 10%, 7% and 3% HE creams treatment. The TNF-α gene expression showed the Histamine and C48/80 induced model were exhibit the reading of gene expression in HE creams treatment comparison to the negative control groups. The morphological findings that all different models which were treated with HE creams had produced an anti-oedematous and reduced the epidermal thickness with similar potential to that of steroid-based hydrocortisone 1% cream. In conclusion, this study highlights the potential antipruritic activity of HE that can be partly attributed to other probable mechanism for skin protective, which warrants further investigation.